Customer Satisfaction and Retention and its impact on Turism in Hotel Industry - Putra Barusman, Andala Rama; Putri Rulian, Evelin (Utopía y Praxis Latinoamericana, 2020)
ABSTRACTTaking a case study of tourism as hospitality industry in Lampung Province in Indonesia, we analyze the impact on customer satisfaction and retention. Using Structural Equation Model (SEM), we find that customer relationship management has a significant impact on service quality, customer satisfaction and customer retention. Relying on the findings, we recommend some strategies for the government of Lampung Province, for example: training local people to behave more friendly in welcoming domestic or international tourists, fixing all lodging facilities, creating more souvenirs with Lampung’s ornaments and developing management system adopting global changes in technology, communication and trend.